The Mirror Image Conflicts Case - Charles R. Haworth (Washington University Law Quarterly, 1974)
Since the 1969 decision of the Missouri Supreme Court in Kennedy v. Dixon, adopting for Missouri the Restatement (Second) of Conflict of Laws, approach to tort choice-of-law cases, only two Missouri cases have raised what can be characterized as difficult tort choice-of-law problems. One of these cases, Griggs v. Riley, presented the Missouri Court of Appeals for the St. Louis District with a factual situation that, when considered by courts of other jurisdictions, has evoked widespread commentary and produced divergent results. The situation arises when a guest and host from an immunity jurisdiction are involved in an accident in a no-immunity jurisdiction. At first glance, the case appears to present merely the “mirror image” of the now classic “false conflict” case, in which a guest and host from a no-immunity jurisdiction are involved in an accident in an immunity jurisdiction. This Article will examine in detail the competing policies at work in the “mirror image” case, using Griggs as the basic fact pattern and analyzing the method of resolution proposed by the Restatement (Second).
Keywords: Conflict of laws – Torts; Immunity; Babcock; Kennedy v. Dixon